Postpartum Hemorrhage and its Associated Factors Among Women who Gave Birth at Yirgalem General Hospital, Sidama Regional State, Ethiopia - Tedla Amanuel (SAGE Publishing, 2021)
Background Globally, postpartum hemorrhage (PPH) is one of the leading causes of maternal mortality. In developing countries, it accounts for more than 30% of all maternal deaths. So, understanding its burden in the health care setting is significant. Thus, this study aimed to assess the magnitude of PPH and its associated factors among women who gave birth at Yirgalem General Hospital, Sidama Region, Ethiopia. Methods A cross-sectional study was conducted from March 12 to 26, 2020 among randomly selected 298 women. Data were collected using an interviewer-administered, structured, and pretested questionnaire. EpiData version 3.1 and SPSS version 20 were used to enter and analyze the data, respectively. Descriptive statistics, bivariable, and multivariable logistic regression analysis were done. Adjusted odds ratio with 95% confidence interval (CI) was used to measure the presence and strength of association between the independent and the outcome variables. A P -value ≤.05 was considered to declare statistical significance. Result The magnitude of PPH was 9.4% [95% CI: 6.0, 12.8]. Prolonged labor (≥24 h) [AOR = 3.4, 95% CI: 1.1, 9.9], giving birth by cesarean section [AOR = 5.8, 95% CI: 1.1, 22.0], and instrumental vaginal delivery [AOR = 3.7, 95% CI: 1.1, 12.7], and having a history of the uterine atony [AOR = 4.8, 95% CI: 1.4, 16.6] during their last delivery were factors significantly associated with PPH. Conclusion The magnitude of PPH was high. Healthcare professionals should manage the progress of labor and take all necessary measures at right time. Also, giving attention to the safety of delivery-related procedures and early related potential risks is crucial.